Effect of neck posture on cervicothoracic loads in overhead crane operators. Issue 1 (2nd January 2021) - Afshari, Davood; Mazloumi, Adel; Nourollahi-Darabad, Maryam; Nasl Saraji, Gabraeil; Rahimi Foroushani, Abbas
Abstract : Awkward neck postures are commonly documented to be associated with an increased risk of neck disorders. This study intended to continuously monitor and evaluate neck postures and to estimate the cervicothoracic loads among overhead crane operators during work time. Neck postures were measured among 40 randomly selected operators by an inclinometer during 2 h of work time. To determine the tasks and adapt the posture recordings to each of their corresponding tasks, direct observation was conducted concurrently. The median neck flexion and lateral bend angles were 28.23° and 11.30°, respectively. The mean compression and shear loads on the neck ranged from 75.22 to 113.14 N and from 9.50 to 41.11 N, respectively. The results indicated substantial levels of exposure to awkward and extreme neck postures among the operators. The nature of the operators' work and the visual requirements of some tasks will increase the mechanical loads on the neck.